Metabolomics of various samples advancing biomarker discovery and pathogenesis elucidation for diabetic retinopathy - Du, Xiaohui; Yang, Le; Kong, Ling; Sun, Ye; Shen, Kunshuang; Cai, Ying; Sun, Hui; Zhang, Bo; Guo, Sifan; Zhang, Aihua; Wang, Xijun (Frontiers in Endocrinology, 2022)
Diabetic retinopathy (DR) is a universal microvascular complication of diabetes mellitus (DM), which is the main reason for global sight damage/loss in middle-aged and/or older people. Current clinical analyses, like Hemoglobin A1c, possess some importance as prognostic indicators for DR severity, but no effective circulating biomarkers are used for DR in the clinic currently, and researches on the latent pathophysiology remain lacking. Recent developments in omics, especially metabolomics, continue to disclose novel potential biomarkers in several fields, including but not limited to DR. Therefore, based on the overview of metabolomics, we reviewed progress in analytical technology of metabolomics, the prominent roles and the current status of biomarkers in DR, and update of potential biomarkers in various DR-related samples via metabolomics, including tear as well as vitreous humor, aqueous humor, retina, plasma, serum, cerebrospinal fluid, urine, feces. In this review, we underscored the in-deep analysis and elucidation of the common biomarkers in different biological samples based on integrated results, namely, alanine, lactate, and glutamine. Alanine may participate in and regulate glucose metabolism through stimulating N-methyl-D-aspartate receptors and subsequently suppressing insulin secretion which was the potential pathogenesis of DR. Abnormal lactate could cause extensive oxidative stress and neuroinflammation, eventually leading to retinal hypoxia and metabolic dysfunction; on the other hand, high-level lactate may damage the structure and function of the retinal endothelial cells barrier via the G protein-coupled receptor 81. Abnormal glutamine indicates disturbance of glutamate recycling, which may affect the activation of Müller cells and proliferation via the PPP1CA/YAP/GS/Gln/mTORC1 pathway.